The Problematics of Law Enforcement in Dice Gambling: An Islamic Criminal Law Analysis in Medan, Indonesia - Abdul Aziz Lubis; Zulpahmi Lubis (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
Although formally prohibited, gambling remains a persistent challenge in societies characterized by plural legal systems. In Medan, dice gambling has evolved into a socially tolerated practice despite its clear legal prohibition. This study aims to analyze the problematics of law enforcement concerning such practices and to examine them from the perspective of Islamic criminal law. This research adopts a qualitative socio-legal approach that integrates doctrinal and empirical analyses through statutory, conceptual, and case-based approaches. Data were obtained through library research and a limited number of semi-structured interviews, and were analyzed iteratively through triangulation between legal norms and social realities. The findings reveal that law enforcement remains inconsistent and ineffective, reflecting a significant gap between law in the books and law in action, exacerbated by social normalization and weak institutional responses. From the perspective of Islamic criminal law, gambling (al-maysir) is strictly prohibited as it contravenes the protection of property and religion. Its classification as a ta‘zīr offense allows for the development of flexible and context-sensitive enforcement models. This study proposes an integrative approach grounded in maqāṣid al-sharīʿah as a normative framework to enhance adaptive and equitable law enforcement.